A comparative study of the organizational structures of three high schools against the model in terms of delegation of functions - Picando, Ananias T. (Animo Repository, 1978)
This project paper aims to design a functional model of delegation of functions for a high school within a complex. The main purpose of this model of delegation is to improve the principals efficiency and effectiveness through delegation and maximum sharing of some of his responsibilities with faculty and staff. It attempts to survey the existing organizational structures of three high schools (Christ the King, Notre Dame of Dadiangas College and Sumulong Memorial High School) in comparison to the model of delegation, in the areas of planning, decision-making, reporting and supervision.